Mechanical Properties of Concrete with Recycled High-Density Polyethylene Macro Flat Fiber and Rice Hull Ash as Partial Replacement to Cement - Principio, Neslyn L.; Demonteverde, Angelo A.; S. Lagradilla, Ian Paolo; D.C. Samson, John Cesar (International Journal of Integrated Engineering, 2022)
This study determines the mechanical properties of concrete with the addition of recycled High-Density Polyethylene (HDPE) Macro Flat Fiber (MFF) and Rice Hull Ash (RHA) as partial replacement to cement. The objective of this study is to identify the optimum mix ratio for compressive and flexural strength of concrete. Various percentage of HDPE MFF (0.5%, 0.75%, and 1.0%) and 10% partial replacement of RHA to cement is incorporated in the mixture. The RHA is obtained through uncontrolled burning while HDPE MFF is collected through shredding and manual cutting. The results showed that the addition of HDPE MFF had a positive effect on the compressive and flexural strength of concrete. The optimum value is achieved on concrete with 0.5% HDPE MFF and no RHA, as it had showed an average of 31.87 MPa with a 18.04% increase in compressive strength, and an average of 4.532 MPa with a 17.78% increase for flexural strength. Moreover, the combination with RHA had not showed promising results. It had been concluded that the addition of recycled HDPE MFF with no RHA increases the compressive and flexural strength of concrete.